Attitudes of university youth towards emigration in light of the war on Syria Tishreen University students as a model - Shaheen, Celine Jameel (Journal of Humanities & Social Sciences, 2023)
The emigration of university youth constitutes a socio-demographic phenomenon that affects developing countries in particular, which makes it a social, economic and security challenge. This phenomenon is becoming more widespread because of the significant deterioration of the security, economic, social and environmental conditions; as war pushes the youth to flee the current circumstances towards a situation that accords with their plans and aspirations. This applies very clearly to the case of Syrian youth in the last decade that was marked by instability. This study sheds light on this category in the actual situation in Syria, due to the significant exacerbation of the phenomenon among young people in our society. The great loss incurred by Syria because of the emigration of qualified and scientifically, medically and professionally experienced youth could not be ignored. The study of their attitudes towards emigration according to their age and professional levels constitute a strong ground through which we could work to find solutions for their problems and activate their role to prevent their emigration. To achieve the purposes of the research, and based on the analytical descriptive approach, the questionnaire was designed, arbitrated and distributed to the research sample of 60 students from Tishreen University as a model for this category in various Syrian universities. The data was analyzed using the SPSS statistical system, and the research results concluded: - There is clearly a statistically significant correlation between some of the studied variables. - There is a clear effect of sex variable in favor of males in wanting to migrate more than females. -The age group (25-29) years was the category that has the most positive attitudes towards emigration. - The results showed the impact of the economic situation as the most important variable motivating young people to emigrate. - On the other hand, the results of the study showed that there was no statistically significant correlation for some of the studied variables: There was no effect for the type of study, specialization (theoretical or applied colleges), place of residence (urban-rural), and the internal displacement variable (linked to the state of war on Syria). Based on the results of the research, the researcher proposed a set of recommendations that aim to reduce the phenomenon of youth emigration in general, and university youth in particular. These included; social and governmental levels. The most important of these recommendations is the need to focus on documenting this phenomenon in official records in Syria, which would help to study it in a more accurate and comprehensive statistical way.